2017
DOI: 10.4103/0253-7176.198946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effect of Antidepressants on Psychomotor Functions

Abstract: Objective:The comparison of the effect of antidepressants on psychomotor functions in patients with endogenous depression.Materials and Methods:This prospective interventional study was carried out at a tertiary care teaching hospital on 95 literate patients with newly diagnosed endogenous depression matching inclusion and exclusion criteria. Patients were prescribed either desvenlafaxine (50 mg) or fluoxetine (40 mg) or sertraline (50 mg). Psychomotor functions were assessed by digit letter substitution, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…On intergroup analysis, the mean HAM-D score was compared between Group F and Group V; it was observed that the difference in mean HAM-D score at 3 rd , 6 th , 9 th , and 12 th weeks interval was clinically as well as statistically nonsignificant. A similar study was conducted by Mendhe et al [12], study revealed that on comparing the efficacy of the antidepressants, all the groups showed a significant reduction in mean scores at the end of the 1 st month and 3 rd month as compared to the baseline values. However, no statistically significant difference was observed at the end of 3 months of treatment among the different groups.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…On intergroup analysis, the mean HAM-D score was compared between Group F and Group V; it was observed that the difference in mean HAM-D score at 3 rd , 6 th , 9 th , and 12 th weeks interval was clinically as well as statistically nonsignificant. A similar study was conducted by Mendhe et al [12], study revealed that on comparing the efficacy of the antidepressants, all the groups showed a significant reduction in mean scores at the end of the 1 st month and 3 rd month as compared to the baseline values. However, no statistically significant difference was observed at the end of 3 months of treatment among the different groups.…”
Section: Discussionsupporting
confidence: 64%
“…However, the importance of the present study cannot be undermined. Studies are available which show the effect of antidepressants on cognitive functions but most of these studies are single-dose studies, and studies of the same class of antidepressants [21].…”
Section: Discussionmentioning
confidence: 99%
“…Patients from Dataset B performed the task both in unmedicated and medicated state, providing a source of practice. Additionally, long-term medication might have induced partial psychomotor performance deficits [72, 73] affecting the procedural baseline levels, and thus also limit its subsequent consolidation. This was not observed in the group with short-term medication, which also showed higher baseline levels and may have benefited from previous training before medication onset.…”
Section: Discussionmentioning
confidence: 99%
“…Because certain drugs can have positive or negative effects on cognitive control and/or psychomotor function (Culang et al, 2009;Mendhe et al, 2017) and interact with rTMS (Breden Crouse, 2014;Hunter et al, 2019), medication effects may have contributed to some of the findings presented here.…”
Section: Effect Of Rtms On Cognitive Controlmentioning
confidence: 91%